PENGEMBANGAN BAHAN AJAR DENGAN EDMODO UNTUK MENINGKATKAN LEVEL BERPIKIR PROBABILISTIK SISWA KELAS VIII SMP NEGERI 12 SURAKARTA - Kurniasih, Rini; Sujadi, Imam; Subanti, Sri (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The purposes of this study were: 1) to determine the process and to get the development of learning materials in accordance with Edmodo, 2) to decide whether the level of students probabilistic thinking that use learning materials with Edmodo better than the level of probabilistic thinking that use the existing learning materials or not.This study is a research and development (R&D). This study is divided into three stages namely the preliminary stage, the development stage and the testing stage or experimentation. Preliminary stage includes research and information collecting. The development stage includes planning and develop preliminary form product, preliminary field testing and main product revision, main field testing and operational product revision, operational filed testing and final product revision. The testing stage includes the qualitative analysis and quantitative analysis with the Kolmogorov-Smirnov test . Data analysis that used is descriptive analysis and the quality of learning materials based on the criteria of validity, practicality and effectiveness of learning materials. Determination of the final product is done by focus group discussion (FGD) between researchers and teachers or practitioners. Based on the study results obtained the following conclusions : 1) the preliminary stage is concluded learners at the level of the subjective and transitional; the development stage is conclude the obtained validity with an average of 3.57 of a media expert, 3.67 of subject matter experts; the practicality has exceeded the criteria above 75 % and the effectiveness gained an average response learners receive is 93.25 %; and from the result of FGD concluded that learning materials can be used in the process of learning in the curriculum 2013 and can be disseminated, 2) learning that use Edmodo learning materials is more effectively to improve the level of probabilistic thinking learners than the learning that use the existing learning materials.Key words: learning material, Edmodo, level, probabilistic thinking